Significant role of antiferromagnetic GdFeO3 on multiferroism of bilayer thin films. (28th February 2018) - Shah, Jyoti; Bhatt, Priyanka; Diana Diana Dayas, K; Kotnala, R K
Abstract: Inversion of BaTiO3 and GdFeO3 thin films in bilayer configuration has been deposited by pulsed laser deposition technique. A significant effect of strain on thin film has been observed by X-ray diffraction analysis. Tensile strain of 1.04% and 0.23% has been calculated by X-ray diffraction results. Higher polarization value 70.4 μ C cm −2 has been observed by strained BaTiO3 film in GdFeO3 /BaTiO3 bilayer film. Strained GdFeO3 film in BaTiO3 /GdFeO3 bilayer configuration exhibited ferromagnetic behaviour showed maximum magnetization value of 50 emu gm −1 . Magnetoelectric coupling coefficient of bilayer films have been carried out by dynamic method. Room temperature magnetoelectric coupling 2500 mV cm −1 -Oe has been obtained for BaTiO3 /GdFeO3 bilayer film. The high ME coupling of the BaTiO3 /GdFeO3 bilayer film reveals strong interfacial coupling between ferroelectric and ferromagnetic dipoles. On magnetoelectric coupling coefficient effect of ferromagnetic GdFeO3 layer has a significant role. Such high value of ME coupling may be useful in realization of magnetoelectric RAM (MeRAM) application.